Strategi Pemulihan Usaha Kerajinan Rotan di Era Pasca Pandemi Covid-19 Pada Usaha Adit Furniture - Chintya Ones Charli; Syahdatul Jumaiyang; Wulan Asri Lestari (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
This study examines the business recovery strategies implemented by Adit Furniture, a rattan craft company, in facing the challenges of the post-COVID-19 pandemic era. The pandemic has had a significant impact on the rattan craft industry, including decreased demand, supply chain disruptions, and changes in consumer preferences. This study uses a qualitative analysis method with a case study approach, where data is collected through direct observation at Adit Furniture's production site and in-depth interviews with the owner, employees, and related stakeholders. Observations were conducted to understand the production process, implementation of health protocols, and operational adaptations, while interviews aimed to gain information about the strategies implemented, challenges faced, and future visions. This study also reveals the challenges faced in the recovery process and the factors that contributed to the success of these strategies. These findings are expected to provide valuable insights for other rattan craft business actors in navigating the post-pandemic business landscape and designing effective recovery strategies.